Studies on Antiulcer Agents. I. Synthesis and Pharmacological Properties of Ethyl 2-((1H-Benzimidazol-2-yl)sulfinylmethyl)-4-dimethylamino-5-pyrimidinecarboxylate, a New H^+/K^+-ATPase Inhibitor Possessing Mucosal Protective Activity - 寺島 幸司; 嶋村 浩; 川瀬 明人; 田中 裕二; 上西 啓司; 木村 伊佐美; 石塚 泰博; 佐藤 誠 (Chemical & pharmaceutical bulletin, 1995)
Ethyl 2-[(1H-benzimidazol-2-yl)sulfinylmethyl]-4-dimethylamino-5-pyrimidinecarboxylate (2) has been synthesized and evaluated for antiulcer properties. Compound 2 is a H^+/K^+-ATPase inhibitor that affords mucosal protection against absolute ethanol-induced gastric lesions in rats after oral and parenteral administrations. On the other hand, omeprazole, a representative H^+/K^+-ATPase inhibitor, showed mucosal protective action only after oral administration, indicating that it required gastric acid secretion to generate activity. The antiulcer activity of 2 in animal models, such as water-immersion stress-induced gastric ulcer in rats and acidified aspirin-induced gastric ulcer in rats, was three times higher than that of cimetidine.